2016
DOI: 10.1371/journal.pone.0163310
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Low Quality Sleep Impairs Postural Control in Healthy Adults

Abstract: The lack of sleep, both in quality and quantity, is an increasing problem in modern society, often related to workload and stress. A number of studies have addressed the effects of acute (total) sleep deprivation on postural control. However, up to date, the effects of chronic sleep deficits, either in quantity or quality, have not been analyzed. Thirty healthy adults participated in the study that consisted of registering activity with a wrist actigraph for more than a week before performing a series of postu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 43 publications
1
55
0
5
Order By: Relevance
“…First, sub-optimal sleep is associated with increased reaction times; 30,32,39 attentional lapses; 29,31 degraded visual tracking; 31,32 reduced postural control and strength; 29,33,40,41 impaired emotional recognition, responsiveness, and control 34 ; and increased impulsivity and risky behavior. [35][36][37] Second, the cardiovascular, 38,39 endurance, 38 strength, 40,41 and accuracy 31,32 components of sport performance are reduced or impaired under inadequate or low quality sleeping conditions as well as daytime sleepiness.…”
Section: Bidirectional Relationships Between Sports-related Concussiomentioning
confidence: 99%
See 1 more Smart Citation
“…First, sub-optimal sleep is associated with increased reaction times; 30,32,39 attentional lapses; 29,31 degraded visual tracking; 31,32 reduced postural control and strength; 29,33,40,41 impaired emotional recognition, responsiveness, and control 34 ; and increased impulsivity and risky behavior. [35][36][37] Second, the cardiovascular, 38,39 endurance, 38 strength, 40,41 and accuracy 31,32 components of sport performance are reduced or impaired under inadequate or low quality sleeping conditions as well as daytime sleepiness.…”
Section: Bidirectional Relationships Between Sports-related Concussiomentioning
confidence: 99%
“…[26][27][28] With respect to athletics, this is especially problematic. Chronic under-sleeping, sleep restriction, and sleep deprivation are associated with, and can result in, mental fatigue; 29,30 attentional lapses; 30,31 increased reaction time; 29,32 impaired predictive visual tracking; 31,32 reduced postural and dynamic motor control; 29,33 degraded intra-and inter-personal emotion regulation, perception, and responsiveness 34 ; and increased impulsivity and risk-taking behavior. [35][36][37] Furthermore, sport performance indices -including cardiovascular, 38,39 endurance, 38 strength, 40,41 and accuracy 31,32 outcomes -are reduced or impaired under inadequate or low quality sleeping conditions as well as daytime sleepiness or fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these recommendations, chronic sleep loss (<5.5 h/night of sleep) in the USA is reaching epidemic levels [ 47 ]. For individuals with chronic sleep loss, the consequences are numerous including increased somatization [ 48 , 49 ], poor emotional processing and responsiveness (e.g., increased incidence of depression and anxiety) [ 50–52 ], impaired cognition (vigilant attention, executive function, working and long-term memory) [ 53–56 ] and poor motor performance [ 57–59 ], as well as increased risk for general health issues including diabetes [ 60–62 ], cardiovascular disease [ 60 , 63 ], neurodegeneration [ 64 , 65 ] and overall poorer quality of life [ 66 ]. While the exact nature of this trend toward chronically undersleeping is not fully understood, work–life stress (e.g., increased expectations for high job-related hours, social stress) as well as the highly prevalent use of fluorescent lighting and blue-shifted light-emitting diode screens at night [ 67–69 ] are all implicated.…”
Section: Mtbis and Their Consequencesmentioning
confidence: 99%
“…Sleep quality influence balance capabilities. For example, a study conducted by Furtado and colleagues demonstrated the individuals with worse sleep quality performed worse on balance test with eyes closed [ 62 ]. Jorgensen and colleagues found that participants who described being “sleepy” had increased postural sway, relative to participants who reported being well-rested [ 63 ].…”
Section: Overviewmentioning
confidence: 99%